Capacitive Field‐Effect Biosensor Applied for the Detection of Acetoin in Alcoholic Beverages and Fermentation Broths. Issue 13 (1st February 2021) - Jablonski, Melanie; Münstermann, Felix; Nork, Jasmina; Molinnus, Denise; Muschallik, Lukas; Bongaerts, Johannes; Wagner, Torsten; Keusgen, Michael; Siegert, Petra; Schöning, Michael J.
Abstract : An acetoin biosensor based on a capacitive electrolyte–insulator–semiconductor (EIS) structure modified with the enzyme acetoin reductase, also known as butane‐2, 3‐diol dehydrogenase ( Bacillus clausii DSM 8716 T ), is applied for acetoin detection in beer, red wine, and fermentation broth samples for the first time. The EIS sensor consists of an Al/p‐Si/SiO2 /Ta2 O5 layer structure with immobilized acetoin reductase on top of the Ta2 O5 transducer layer by means of crosslinking via glutaraldehyde. The unmodified and enzyme‐modified sensors are electrochemically characterized by means of leakage current, capacitance–voltage, and constant capacitance methods, respectively. Abstract : A field‐effect acetoin biosensor modified with the enzyme acetoin reductase ( Bacillus clausii DSM 8716 T ) is applied for the detection of acetoin in beer, red wine, and fermentation broth samples. The enzyme is immobilized via a cross‐linker on the transducer layer of an electrolyte–insulator–semiconductor (EIS) sensor consisting of an Al/p‐Si/SiO2 /Ta2 O5 layer structure.